Cigarette smoking during an N-acetylcysteine-assisted cannabis cessation trial in adolescents. (July 2014) - McClure, Erin A.; Baker, Nathaniel L.; Gray, Kevin M.
Abstract Background and objectives: Tobacco and cannabis use are both highly prevalent worldwide. Their co-use is also common in adults and adolescents. Despite this frequent co-occurrence, cessation from both substances is rarely addressed in randomized clinical trials. Given evidence that tobacco use may increase during cannabis cessation attempts, and additionally that tobacco users have poorer cannabis cessation outcomes, we explored tobacco outcomes, specifically cigarette smoking, from an adolescent cannabis cessation trial that tested the efficacy of N-acetylesteine (NAC). Methods: Cannabis-dependent adolescents (ages 15–21; n = 116) interested in cannabis treatment were randomized to NAC (1200 mg bid) or matched placebo for 8 weeks. Participants did not need to be cigarette smokers or be interested in smoking cessation to qualify for inclusion. Results: Approximately 59% of enrolled participants were daily and non-daily cigarette smokers, and only differed from non-smoking participants on the compulsion sub-scale of the Marijuana Craving Questionnaire. Among cigarette smokers who were retained in the study, there was no change in cigarettes per day for either NAC or placebo groups during the eight-week treatment phase. Being a cigarette smoker did not appear to influence the effects of NAC on cannabis abstinence, though there was a trend in the placebo group of poorer cannabis outcomes for cigarette smokers vs. non-smokers. Conclusions: No evidence was found of compensatory cigarette smoking during this cannabis cessation trial in adolescents. Further work assessing interventions to reduce both cannabis and tobacco use in this population is greatly needed.